Critical appraisal of appropriate method for early detection of hearing impairment in newborns in a tertiary care centre - Pasupathy, Sekar; Kumar, Haritha S. (International Journal of Contemporary Pediatrics, 2018)
Background: Hearing plays a vital role in developmental of a child. Hearing loss not only affects the speech and language development of a child but also affects the social, emotional and intellectual development. Hearing is important in the first 2 years of life as this is the critical period for language acquisition. Thereby early detection and intervention for hearing loss is recommended. However, there are no standard protocols for newborn hearing screening. Hence, this study is undertaken to evaluate the appropriate protocol for early detection of hearing impairment in newborns and to ascertain the sensitivity and specificity of Distortion Product Oto-acoustic Emission (DPOAE) and Auditory Brainstem Response (ABR). Methods: A prospective study was conducted in the Department of Paediatrics and Department of Audiology and Speech Pathology in SRM Medical College Hospital and Research Centre. A total of 122 neonates were screened for hearing loss using both DPOAE and ABR before discharge from the hospital. A rescreening with ABR after 1 month was done for those infants who had hearing loss at the initial screening. Results: The study revealed that 16.4% of infants had hearing loss. The referral rate of DPOAE was 54.1% and ABR was 16.4%. ABR had higher passing rates when compared to DPOAE. In a combined screening with both DPOAE and ABR, 17 (13.9%) babies had failed DPOAE with abnormal hearing in ABR (True positives), 49 (40.2%) babies failed DPOAE but had normal hearing in ABR (False positives), 3 (2.5%) babies passed DPOAE but had hearing loss in ABR (False negatives) and 53 (43.4%) babies passed DPOAE and had normal hearing in ABR (True negatives). The association between the results of DPOAE and ABR was statistically significant (0.002). Auditory neuropathy was detected in 3 out of 122 neonates. All these 3 babies belonged to high-risk population. The prevalence of auditory neuropathy is 2.5% which is much lower when compared to other studies. The sensitivity and specificity of DPOAE is 85% and 51.9% respectively. The sensitivity and specificity of ABR was 100%. Conclusions: Present study concludes that the use of combination protocol using both DPOAE and ABR identifies babies with auditory neuropathy spectrum disorder and also ensures high sensitivity and acceptable specificity. Thus, helps in early identification and intervention of congenital hearing loss.